Sodium-Glucose Cotransporter 2 Inhibitors Improve Chronic Diabetic Macular Edema - Yoko Takatsuna; Ryoichi Ishibashi; Tomoaki Tatsumi; Masaya Koshizaka; Takayuki Baba; Shuichi Yamamoto; Koutaro Yokote (Case Reports in Ophthalmological Medicine)
Purpose. Diabetic macular edema (DME) is a vision-threatening condition that develops in diabetic patients. The first-line therapy for DME is intravitreal injections of antivascular endothelial growth factor (anti-VEGF) agents; however, the high frequency of repeat injections, invasiveness of the procedure, and high cost are drawbacks for this treatment. The purpose of this report is to present our findings in 3 patients with chronic DME whose edema was resolved soon after oral doses of sodium-glucose cotransporter-2 (SGLT2) inhibitors were used. Case Presentation. Case 1 was a 66-year-old woman diagnosed with moderate nonproliferative diabetic retinopathy (DR) with DME that had developed a decade earlier. The DME persisted for 4 years in the left eye. The addition of oral empagliflozin, a SGLT2 inhibitor, led to a marked improvement of the DME after one month, and this improvement continued over two years. Case 2 was a 68-year-old woman who was diagnosed with preproliferative DR with bilateral DME. The addition of oral dapagliflozin led to the improvement of the DME after two months, and this improvement continued over one year. Case 3 was a 61-year-old woman who was diagnosed with moderate nonproliferative DR with DME. Oral luseogliflozin was given which led to better glycemic control, and her left central retinal thickness (CRT) was markedly reduced after only two weeks. This reduction was maintained in her left eye for six months without any additional ophthalmic procedures. Conclusions. Although this study involved only three cases, our findings indicate that SGLT2 inhibitors might have possible efficacy for chronic DME.